(untitled) (Revista de História Regional, 2007)
To write political history - either of the practice or the theory, either of the politics in the meaning of the event present in the public or the private one, in the social structures as well as in the capillary of the daily life - means to con-demn the radical relativism that devastates our area, means to recognize an ob-jective reality and the possible connections between it and the concepts that represents it and, at the same time, mold it. Today occurs with history politics, more than with the other tasks of Clio, an attachment to the event, the happening and its unfoldings. However, let us not confuse this approach with a new fall into the ’histoire événementielle’. The question is diverse: if in the birth of the modern times the promotion of the State demanded a total submission of the historiogra-phy, on the point of all production to be identified with history politics, now, when this very State enters in crisis perhaps terminal, the discipline (certainly obliged to renew itself, to develop new methods, to modify sensibilities, to pick-up symbologies and to extend itself to new areas) must be responsible for think-ing this crisis and evaluating its understandings. Therefore more critical than never, it is necessary that the historian assumes the role of adversary of the cul-tural relativism that devastates its specialty and take standings. It is about a new and creative commitment that does not excuse from a constant and accelerated self valuation.